Adverse Drug Reactions in Breastfed Infants: A Cross-Sectional Study of Lactating Mothers - Ahmadzai, Hilai; Tee, Lisa; Crowe, Andrew (MARY ANN LIEBERT, INC, 2022)
Background: Breastfeeding-related adverse drug reactions (ADRs) are thought to be uncommon as reported cases are globally low. The nonspecific nature of these reactions and a lack of awareness and difficulty in identification of ADRs by mothers and clinicians may result in these ADRs being underreported. Aims: This study hypothesized that breastfeeding-related infant ADRs are more frequent than reported. As a first-hand account of breastfeeding mothers, this study aimed to evaluate the impact of the perceived ADRs on the continuation of breastfeeding and maternal treatment. Methods: Women currently breastfeeding or having breastfed in the last 12 months were invited to complete an online survey. The survey comprised 42 questions in 5 sections to obtain data from breastfeeding mothers, including their use of medicines during lactation, perceptions of infant adverse reactions attributable to maternal medication use and its potential impact on breastfeeding. Results: This online survey was completed by 339 women, 42% of whom reported taking at least one medication during breastfeeding. ADRs were reported in 23 infants where a possible or probable causal relationship indicated by a Naranjo score of 1-8 was established in 16 (11.3%). Antibiotics (n = 12) and opioids (n = 2), including tramadol and oxycodone were identified as the most common adverse reaction-causing drugs. The average age of infants at the time of the perceived ADR was 25.6 days (95% confidence interval; 4-85 days; median age 17.5 days). Conclusion: Suspected ADR reporting in this study was significantly greater than those reported to the regulatory body, the Australian Therapeutics Goods Administration, which shows that common breastfeeding-related infant ADRs are underreported.